2021
DOI: 10.1371/journal.pntd.0009527
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and numerical simulation of rabies spreading from canines to various human populations in mainland China

Abstract: Background The mortality of humans due to rabies in China has been declining in recent years, but it is still a significant public health problem. According to the global framework, China strives to achieve the goal of eliminating human rabies before 2030. Methods We reviewed the epidemiology of human deaths from rabies in mainland China from 2004 to 2018. We identified high risk regions, age and occupational groups, and used a continuous deterministic susceptibility-exposure-infection-recovery (SEIR) model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
2
1
0
Order By: Relevance
“…Our estimates of R t calculated from detected clusters of rabies cases were consistent with other studies, with R 0 in rabies outbreaks from around the world previously reported to range between 1.05 and 1.85 (Dürr & Ward, 2015;Hampson et al, 2009;Lu et al, 2021) (even higher R 0 such as 1.62-2.33 (Coleman & Dye, 1996) and 2.42 (Kurosawa et al, 2017) have been reported). R 0 can be calculated using R t if the proportion of the dog population that was susceptible S t is available; however, dog vaccination records were only reported in Tokyo, and numbers of unregistered and free-roaming dogs are not known.…”
Section: Discussionsupporting
confidence: 91%
“…Our estimates of R t calculated from detected clusters of rabies cases were consistent with other studies, with R 0 in rabies outbreaks from around the world previously reported to range between 1.05 and 1.85 (Dürr & Ward, 2015;Hampson et al, 2009;Lu et al, 2021) (even higher R 0 such as 1.62-2.33 (Coleman & Dye, 1996) and 2.42 (Kurosawa et al, 2017) have been reported). R 0 can be calculated using R t if the proportion of the dog population that was susceptible S t is available; however, dog vaccination records were only reported in Tokyo, and numbers of unregistered and free-roaming dogs are not known.…”
Section: Discussionsupporting
confidence: 91%
“…The values seem consistent with values used in other papers modeling rabies such as Lu et al. ( 2021 ), Zinsstag et al. ( 2009 ), Hampson et al.…”
Section: Mathematical Modelsupporting
confidence: 90%
“…According to WHO, the rabies outbreaks have routinely been recorded in China, and the number of rabies cases in humans in different region of China is shown in Figure 1 (2014–2018), demonstrating that rabies is a constant public health threat in China [ 12 , 13 , 14 ]. According to the statistics, the number of rabies deaths in China peaked in 2007 with 3300 cases and declined to 290 cases in 2019 [ 1 , 15 ]. The main reasons for the decrease in mortality are the government’s management of post-exposure prophylaxis (PEP) and the increased level of rabies-related knowledge and awareness, which has led to more people making timely and relevant post-exposure management measures [ 12 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%